Impact of the extracellular matrix on plasticity in juvenile and adult brains. Extracellular matrix and brain plasticity Einfluss der Extrazellulären Matrix auf plastische Prozesse in jungen und alten Gehirnen: Extraxelluläre matrix und Hirnplastizität - Frischknecht, Renato; Happel, Max F.K. (Neuroforum, 2016)
In the higher vertebrate brain, the delicate balance between structural stabilization and remodeling of synaptic networks changes over the life span. The juvenile brain is characterized by high structural plasticity. A critical step in brain maturation is the occurrence of the extracellular matrix (ECM) that structurally stabilizes neuronal tissue restricting the potential for neuronal remodeling and regeneration. Current research has only begun to understand how this putative limitation of adult neuronal plasticity might impact on learning-related plasticity, lifelong memory reformation and higher cognitive functions. In this review, we summarize recent evidence that recognizes the ECM and its activity-dependent modulation as a key regulator of learning-related plasticity in the adult brain. Experimental modulation of the ECM in local neuronal circuits further opens short term windows of activity-dependent reorganization promoting complex forms of cognitive flexible adaptation of valuable behavioral options. This further bears implications for guided neuroplasticity with regenerative and therapeutic potential.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Cortex; Learning; Memory; Plasticity; Protein turnover